La tecnología digital, aprendizaje y educación: prácticas y percepciones de niños menores de 8 años y sus padres - Brito, Rita (2021)
This article discusses the practices and perceptions of children under 8 years old and their families about the use of digital technologies in schools and their potential for learning. The empirical study compares two age groups - children from 3 to 5 years (preschool), and children from 6 to 8 years (primary school). Data was collected through activities with children and interviews with the families, and then worked through a qualitative content analysis. The use of digital technologies in schools has more impact on children attending primary school that in preschool. In addition, the educational potential of devices like the computer and the tablet are underused in school context as in homes. The main explanation for this poor performance lies in the perception of their parents and children about digital technologies, school and learning.